Antioxidant Property of a Novel Lemongrass Oil Mouth Wash: An Experimental Study - Kamath2, Madhur Aggarwal2, Meghna A. Bhandarkar2, B.S. Mahima2, Sonal Sukreeth2, K. Meena Anand1*, Ruchika Goyal1, G. Subraya Bhat1, Shobha (Recent Research in Science and Technology, 2011)
Oxidative stress is believed to be in part responsible for the inflammatory conditions affecting the periodontium manifesting as gingivitis and periodontitis. Antioxidants are those substances which when present in minimum quantities prevents the oxidation of a substrate. Recently, there has been a considerable interest in finding natural antioxidants from plants. Natural antioxidants are presumed to be safe since they occur in plant foods. These natural antioxidants occur in all higher plants, and in all parts of plants. The aim of our study was to compare the efficacy of lemongrass oil mouthwash for anti oxidant property by estimation of thiol levels before and after administration of lemongrass oil mouthwash. A total of 40 subjects were included in this study. Subjects were divided into 4 groups i.e. 3 test groups and one control group. Initially, saliva and gingival crevicular fluid (GCF) were collected and sent for analyzing the thiol levels. After scaling, lemongrass oil mouthwash that was prepared indigenously was administered at three different concentrations. Subjects were recalled on the 15th day; saliva and GCF sample were collected and sent for estimation of thiol levels. Statistical analysis was done using SPSS 16.0 software and results were analyzed. There was no statistical difference in the thiol levels within the case groups whereas the subjects in the case group showed increased thiol levels when compared to the control group. The lemongrass oil mouthwash was found to have anti oxidant activity at all the three concentrations levels.